CLINICO-EPIDEMIOLOGICAL PROFILE OF COVID-19 PATIENTS ADMITTED TO TERTIARY CARE MEDICAL COLLEGE HOSPITAL IN SOUTH INDIA - MURALI T; GOKULA KRISHNAN; BALKEES BEVI; SARANYA; PRABHU; SELVARAJAN N (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This is a retrospective study done in tertiary care medical college hospital in south India to look for clinico-epidemiological profile of coronavirus disease 2019 (COVID-19) patients admitted to the intensive care unit (ICU). This study can help us in identifying the risk factors leading to increased mortality. Hence, identifying these factors can help us in modifying the treatment depending on the risk factors that are present. Methods: All patients who are diagnosed with COVID-19 with reverse transcription polymerase chain reaction positivity admitted to ICU are enrolled. Data are collected retrospectively by analyzing the medical case records and looking for all parameters, such as age, sex, underlying comorbidity, method of oxygen therapy, degree of severity, and inflammatory markers. All these data are analyzed and compared between survivors and non-survivors. Results: 81% were male patients in comparison to female patients contributing to 19%. 55% were <60 years and 45% were >60 years. Non-survivors had a mean age of 64.5 years. Average days of hospital admission, ICU admission, and onset of hypoxia after symptom onset were 4.2 days, 8.5 days, and 7.8 days, respectively. Average PaO2 and P/F ratio was 81.25 and 165.9, respectively. The average P/F ratio in non-survivors was 144 compared to survivors having 187. The average high-resolution computed tomography score on admission and discharge was 12.4 and 11.9, respectively. Regarding inflammatory markers average lactate dehydrogenase (LDH), Ferritin, and interleukin-6 were 462, 618.2, and 130.56, respectively. Non-survivors had increased LDH with a mean of 538.3 when compared to survivors having a mean of 421.4. Conclusion: This study showed that there is increased mortality with an increase in age, especially >60 years. Severe respiratory failure with P/F ratio<144 had increased mortality. Patients with increased LDH showed an increase in mortality.